1988
DOI: 10.1021/ma00180a015
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state CP/MAS carbon-13 NMR study of thermotropic aromatic polyester containing a flexible spacer in the main chain

Abstract: The solid-state structure of a thermotropic aromatic polyester containing an aliphatic flexible spacer based on terephthalic acid and 4,4'-dihydoxy-1,6-diphenoxyhexane has been investigated by highresolution solid-state CP/MAS (cross polarization/magic angle spinning) 13C NMR. Samples of the polymer with different thermal histories, i.e., an original sample as obtained by low-temperature solution polymerization and once-melted samples with different cooling conditions, have been prepared in order to study the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 14 publications
(19 reference statements)
1
24
0
Order By: Relevance
“…25, No. 1,1993 transition of crystalline-isotropic melt. In order to know how the hydrogen bonding interaction affects the formation of mesophases in polyurethanes 3, thermal processing IR measurements were carried out.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…25, No. 1,1993 transition of crystalline-isotropic melt. In order to know how the hydrogen bonding interaction affects the formation of mesophases in polyurethanes 3, thermal processing IR measurements were carried out.…”
Section: Resultsmentioning
confidence: 99%
“…The degree of crystallinity was measured on powder samples by a diffraction of Macscience Co. type MXP 18V using radiation. The scattering intensity was registered at 2° min- 1 for values of 2 e ranging from 4° to 40°. The small-angle X-ray diffraction pattern of 3e was taken in the solid phase, that prepared from quenching rapidly to liquid nitrogen just after annealed at 170°C for 30 min.…”
Section: Diolmentioning
confidence: 99%
“…The peak assignment was carried out according to the literature. 19,20 Comparing the spectrum (C) for the crosslinked, EB-polymerized polymer with the spectrum (B) for the soluble polymer, there was little difference between both solid-state spectra, though the former spectrum exhibited high noise level. Thus, it was suggested that the crosslinking might be caused by a small degree of scission of the epoxy group which was not detectable by NMR spectroscopy or by a reaction caused by an activated epoxy group.…”
Section: Resultsmentioning
confidence: 99%
“…The decrease of the tensile strength may result from the relaxation of molecular orientation which is caused by easy molecular motion by long time annealing at 220°C. Uryu et al 18 reported that the chain conformation transforms from trans to gauche by long time annealing for the TLC polymer with the flexible spacers. The change of conformation occurs the relaxation of molecular orientation.…”
Section: Heat Treatment Of the Polyesteramide Fibersmentioning
confidence: 99%